Listen with the ear of the heart : music and monastery life at Weston Priory - Guarino, Maria S. (Eastman/Rochester studies in ethnomusicology ;, 2018)
A contemplative 'ethnographic study of a Benedictine monastery in Vermont known for its folk-inspired music.'